Impact of an organic formulation (panchakavya) on the bioleaching of copper and lead in contaminated mine soil. (November 2015) - Praburaman, Loganathan; Park, Jung-Hee; Govarthanan, Muthusamy; Selvankumar, Thangaswamy; Oh, Sae-Gang; Jang, Jum-Suk; Cho, Min; Kamala-Kannan, S.; Oh, Byung-Taek
Highlights: Pb and Cu were successfully leached from the contaminated mine soil using organic formulation, panchakavya. Box–Behnken design was used to optimize the experimental conditions. Exchangeable fraction of Pb was significantly increased in the panchakavya-treated soil. HPLC analysis confirmed the presence of different organic acids in panchakavya. A significant increase in the soil extracellular enzyme activities was observed in the leached soil. Abstract: The study was aimed to evaluate the potential of organic formulation, panchakavya, for enhancing the biological leaching of Pb and Cu in contaminated mine soil. Response surface methodology based Box–Behnken design was used to optimize the variables such as incubation time, panchakavya concentration, and agitation rate. The maximum bioleaching (Pb = 64% and Cu = 49%) was observed after 54 h of incubation with 10 mL panchakavya at 120 rpm. Statistics-based contour and three-dimensional plots were generated to understand the relationship between Pb and Cu bioleaching and variables. High-performance liquid chromatography analysis showed the presence of lactic (25.88 mg g −1 ), citric (0.14 mg g −1 ), succinic (0.14 mg g −1 ), malic (0.66 mg g −1 ), and acetic (0.44 mg g −1 ) acids in panchakavya, which may have a vital role in the removal of metals from the contaminated soil. Soil fraction studies indicate a significant increase of Pb (45%) in the exchangeable fraction of panchakavya-treated soil. XRD studies confirmed the role of panchakavya induced calcite and other minerals in the precipitation of metal ions. A significant increase in the enzyme activities of phosphatase, dehydrogenase, urease, amylase, invertase, and cellulase were observed in the panchakavya-treated soil.